Al Muhassinat al Lafdziyyah al-Ma'nawiyah - Raswan, Raswan (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2012)
Study of badi has passed through various phases of the term. Badi 'grow and develop into a big lead and then retreating to his study and pragmatic. The first person credited codify badi 'is Ibn Mu'taz, then badi' is analyzed theby the exciting and challenging to Abdu al-an-Nabulisi Ghaniy formulated more than 160 scientific studied on badi'. Subsequent devlopment of science badi' orientation to orientation decreased pragmatic, not unlike just memorizing rules and unable to come to tadzawwuq balaghi.Study of badi'increasingly leaving only a few studies have considered the main pragmatic language in the Koran dive like the one in the book such as al-al-Wadhihah Balaghah, Jawahir al-Balagha, Jauhar al-Maknun etc.. Balaghah studies are still in existence and is considered the primary will be presented in this article.